Rumination Time and Frequency of Goat Supplemented with Garlic Powder and Organic Chromium - Munasik, Munasik; Bahrun, Bahrun; Sigar, Ihsan Yosinanda; Setyaningrum, Agustinah; Prayitno, Caribu Hadi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
This research investigated the effect of supplementing garlic powder and organic micromineral Cr in feed on rumination time and frequency in Ettawah goat (PE). The research was conducted in Gunung Tugel Farm in Patikraja and the Laboratory of Feed Technology in Faculty of Animal Science, Universitas Jenderal Soedirman, Purwokerto, Central Java. This study used 18 male PE aged 1-1.5 years and weighed 18.62 – 22.69 kg. The feed consisted of 60% concentrate and 40% forage (field grass). Other materials included drinking water, 250 ppm garlic powder (Allium sativum), 1.5 ppm organic chromium mineral and eight CCTV camera. The observed parameters were rumination time and frequency. An in vivo experiment in a Completely Randomised Design (CRD) administered three treatments and six replicates, namely R0: control (basal feed); R1: basal feed + 250 ppm garlic powder; and R2: basal feed + 250 ppm garlic powder + 1.5 ppm organic Cr. The result demonstrated a significantly different effect of garlic powder and organic Cr micromineral supplement on rumination time across treatments, i.e. 404 ± 19.6; 382 ± 19.04 and 351 ± 13.87 min/day, respectively, or 379 min/day on average. Rumination frequency was not significantly different across R0, R1, and R2 namely 360 ± 24.03; 359 ± 30.13 and 342 ± 21.10 times/day, respectively. Conclusively, garlic powder and organic Cr micromineral significantly affected rumination time, but not significantly affected rumination frequency of PE goat.